1984
DOI: 10.1002/ps.2780150110
|View full text |Cite
|
Sign up to set email alerts
|

The enantiomeric composition of triadimenol produced during metabolism of triadimefon by fungi. Part I: Influence of dose and time of incubation

Abstract: Botrytis cinerea, grown in shake culture in a liquid nutrient medium containing different amounts of triadimefon (4–40 mg litre−1), produced triadimenol as the sole major metabolite. Analysis by gas‐liquid chromatography (g.l.c.) showed the presence of (1R,2S) and (1S,2S)‐triadimenol, but no (1S,2R) or (1R,2R)‐enantiomer. The proportion of (1R,2S) to (1S,2S)‐triadimenol decreased over the period 6 to 168 h and with increased amounts of applied triadimefon. The implications of these patterns of metabolism are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…However, over a 30 day period in nonsterile soils, 64-80% of triadimefon was degraded. Earlier reports suggested that soil microorganisms have the ability to degrade triadimefon (6,12,18). Laboratory shake cultures of Aspergillus niger converted 5-32% of triadimefon to triadimenol in 2-5 days (6), with no further metabolism of triadimenol being detected.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, over a 30 day period in nonsterile soils, 64-80% of triadimefon was degraded. Earlier reports suggested that soil microorganisms have the ability to degrade triadimefon (6,12,18). Laboratory shake cultures of Aspergillus niger converted 5-32% of triadimefon to triadimenol in 2-5 days (6), with no further metabolism of triadimenol being detected.…”
Section: Resultsmentioning
confidence: 93%
“…However, triadimefon incubated with mycelia mats of A. niger was metabolized to its isopropyl derivative [1-(4-chlorophenol)-3-methyl-1-(1 H -1,2,4-triazol-1-yl)-2-butanone]. Deas et al ( , ) studied triadimefon metabolism using different fungi, viz. Coriolus versicolor , Cladosporium cucumerinum , Botrytis cinerea , and Fusarium culmorum , and triadimenol was recovered as the only metabolite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its biological reduction to triadimenol {( 1 -(4-chlorophenoxy)-3,3-dimethy 1-1 -( 1H-1,2,4-triazol-1 -yl)butan-2-ol)}, also very active against rusts and other fungi, has been reported in several studies [11,12,13]. Earlier studies have described the photolysis of triadimefon in methanol [11] and in aqueous solutions of humic and ful vie acids [14].…”
Section: Introductionmentioning
confidence: 94%
“…7,8 It also suspected to have endocrine disrupting effect, neurotoxic and carcinogenic in mature rodent models. Considering triazole pesticides have stereoselective degradation behavior in mammals [9][10][11] ; this toxicity of triazole fungicide could also have stereoselectivity.…”
Section: Introductionmentioning
confidence: 99%